AN EMPIRICAL STUDY ON THE MARKET ORIENTED PRACTICES BY AYURVEDA PHARMACUETICAL INDUSTRY IN KERALA - CHANDRASEKAR, KS; PUSHPAN, BIJU (International Journal of Psychosocial Rehabilitation, 2020)
The Ayurveda pharma industry in Kerala is dominated by the existence of traditionally organized marketing departments. There exist specialised functional departments and specialised functions in these companies – marketing, sales, and production and so on. This study was intended to find the marketing oriented practices of such companies in Kerala and other market places. The general managers and above responsible for the marketing were identified as the target respondents. Literature review in this context was undertaken and also an inferential analysis was conducted to see whether marketing orientation is there. The findings of the study reveal that there is a need for marketing by ayurveda pharmaceutical companies and the same was documented x The Ayurveda pharma industry in Kerala is dominated by the existence of traditionally organized marketing departments. There exist specialised functional departments and specialised functions in these companies – marketing, sales, and production and so on. This study was intended to find the marketing oriented practices of such companies in Kerala and other market places. The general managers and above responsible for the marketing were identified as the target respondents. Literature review in this context was undertaken and also an inferential analysis was conducted to see whether marketing orientation is there. The findings of the study reveal that there is a need for marketing by ayurveda pharmaceutical companies and the same was documented